1988
DOI: 10.1056/nejm198808253190801
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiologic Study of Mortality among Bereaved Parents

Abstract: To study the health consequences of parental bereavement, we compared the mortality in two groups of bereaved Israeli parents with that in the general population. One cohort comprised the parents of all 2518 soldiers 18 to 40 years of age who were killed during the Yom Kippur War in 1973. The second consisted of the parents of 1128 men 18 to 30 years of age who died in accidents between 1971 and 1975. Both groups were followed through 1983. The comparison population was the entire population of Jewish Israelis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
2
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 18 publications
3
43
2
1
Order By: Relevance
“…This finding is consistent with a number of studies (Cleiren et al, 1994;Leahy, 1992;Levav et al, 1988;Nolen-Hoeksema & Larson, 1999;Sanders, 1979), which have consistently shown that the loss of an adult child might result in more intense or persistent grief than any other type of loss.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with a number of studies (Cleiren et al, 1994;Leahy, 1992;Levav et al, 1988;Nolen-Hoeksema & Larson, 1999;Sanders, 1979), which have consistently shown that the loss of an adult child might result in more intense or persistent grief than any other type of loss.…”
Section: Discussionsupporting
confidence: 91%
“…This finding was replicated in non-U.S. populations in Israel (Levav, Friedlander, Kark, & Peroz, 1988) and The Netherlands (Cleiren et al, 1994). A recent study (Shear, Frank, Houck, & Reynolds, 2005) found that parents who lost a child showed a much lower response to complicated grief treatment as compared to patients who experienced other types of loss (17% vs. 60%, respectively).…”
mentioning
confidence: 84%
“…Indeed, the death of a child can be a devastating event: parents may feel overwhelmed by feelings of guilt and helplessness, manifestations of grief may well last for a lifetime, and if the marriage has been full of conflicts it often disintegrates and ends up in divorce [1]. However, a recent large epidemiologic study did not provide evidence of increased mortality among parents who lost a son of adult age in the war or because of an accident, although the subgroup of widowed and divorced parents did have increased mortality, a result reaching statistical significance in mothers [22]. This find ing may suggest an interaction between parental and mar ital bereavement, possibly related to the absence of spou sal support during parental bereavement.…”
Section: Factors Influencing Bereavement Reactionsmentioning
confidence: 99%
“…Additionally, we obtained the parent's birth date, country of origin, year of immigration when appropriate, and date and cause of death. Although these data were already available, 30 for reliability, the linkage and all information were confirmed.…”
Section: The Bereavedmentioning
confidence: 88%